Pembaharuan Keabsahan Pembuktian Testimonium de Auditu dalam Tindak Pidana Kekerasan Seksual: Analisis Peraturan Perundang-Undangan di Indonesia - Feni, Evita; Yunara, Edi; Desiandri, Yati Sharfina (IAIN Langsa, 2024)
Ideally, the validity of Testimonium de Auditu evidence in cases of sexual violence should provide stronger legal protection for victims, given that sexual violence often occurs in closed situations without direct witnesses. However, in reality, Testimonium de Auditu has long been considered to have insufficient evidentiary strength in Indonesian criminal law, leading to its frequent disregard in law enforcement processes. This research focuses on how regulatory changes in Indonesia have accommodated and strengthened the validity of Testimonium de Auditu in the context of sexual violence crimes. This study aims to analyze the renewal of the validity of Testimonium de Auditu evidence in sexual violence crimes based on the perspective of Indonesian legislation. The research is classified as a qualitative literature study, utilizing a normative legal approach. The findings indicate that the reforms outlined in the Indonesian Criminal Code (KUHP), Constitutional Court Decision Number 65/PUU-VIII/2010, and Law Number 12 of 2022 on Sexual Violence Crimes (UU TPKS) have strengthened the position of Testimonium de Auditu as valid evidence in cases of sexual violence. These reforms allow Testimonium de Auditu to be recognized and more adaptive within the criminal justice system, particularly in addressing the challenges of proving sexual violence, which often lacks direct witnesses.